Autoimmune-Like Hepatitis: A "Hepatitic" Manifestation of Chronic Graft Versus Host Disease in Post–Stem Cell Transplant. (April 2016) - Baniak, Nick M.; Kanthan, Rani
A 59-year-old female received a matched related donor stem cell transplant for chronic myelogenous leukemia. After being successfully treated with prednisone for chronic graft versus host disease that initially started 50 days posttransplant, she developed hepatic dysfunction during the steroid taper on day 531, as evidenced by jaundice, elevated liver enzymes, and increased bilirubin. Liver biopsy showed histology suggestive of autoimmune-like hepatitis, which is a rare manifestation of chronic "hepatitic" graft versus host disease.